Determinants of internationalization of SMEs using partial least square / Zahariah Mohd Zain, Azurin Sani and Ahmad Shazeer Mohamed Thaheer - Mohd Zain, Zahariah; Sani, Azurin; Mohamed Thaheer, Ahmad Shazeer (Universiti Teknologi Mara Selangor, 2020)
Internationalization provides various strategic benefits to the SMEs. It might increase the firm's sales and revenue and be able to sustain in the economy for a longer period. However, the lack of information may become a challenge to the business, thus it is not easy to carry out the internationalization successfully due to limited resources and capabilities. On the other hand, influential factors on SMEs internalization have been discussed in developed countries, yet some developing countries are still struggling for empirical evidence. Some SMEs are facing difficulties in entering the global market as they have zero or less information on it while some of them successfully entered the market and can compete internationally. This indicates that every SMEs has the opportunity to internationalize their goods or services with proper understanding and better information about the global market. Prior studies have been carried out on factors influencing internationalization of SMEs however this study has been done specifically on internationalization of the SMEs in Malaysia. The determinants of internationalization investigated are internal factors, external factors, and networking, using partial least square method. The outcome of this study indicated that external factors, internal factors, and networking do not have any significant relationship with SMEs decision to internationalize.